2008
DOI: 10.1007/s00431-008-0802-2
|View full text |Cite
|
Sign up to set email alerts
|

The association of elevated alanine aminotransferase and the metabolic syndrome in an overweight and obese pediatric population of multi-ethnic origin

Abstract: We studied the association between alanine aminotransferase (ALT) and features of the metabolic syndrome in a cohort of overweight and obese children aged 3-18 years. An oral glucose tolerance test was performed in 443 consecutive children from an obesity out-patient clinic (median age 11.2, range 3.1-18.0 years; n=240 boys) of multi-ethnic origin. The prevalence of the metabolic syndrome, insulin resistance, elevated ALT (>30 IU/L), and the association of ALT with (components of) the metabolic syndrome was as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
3
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 28 publications
4
31
3
2
Order By: Relevance
“…Thus, we hypothesize that insulin resistance has not started yet in our patients groups. We found lower adiponectin levels in our patients and this is consistent with previous studies [4,33]. Previous studies suggest that hypoadiponectinemia might be involved in the development of FLD [4,24].…”
Section: Discussionsupporting
confidence: 95%
See 1 more Smart Citation
“…Thus, we hypothesize that insulin resistance has not started yet in our patients groups. We found lower adiponectin levels in our patients and this is consistent with previous studies [4,33]. Previous studies suggest that hypoadiponectinemia might be involved in the development of FLD [4,24].…”
Section: Discussionsupporting
confidence: 95%
“…At the same time, low HDL-C level is an independent predictor for presence of FL. Low HDL levels were highly associated with the metabolic syndrome, insulin resistance, and high triglycerides in obese children and adolescents in recent studies [33,36]. High risk of FL, in our Doppler US group, was associated with alterations in lipid metabolism but not with glucose metabolism in overweight and obese adolescents.…”
Section: Discussionmentioning
confidence: 58%
“…On the basis of the German guidelines for diagnosis and treatment of OW children and adolescents, 13 [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19].98 years, 58% males) were examined and evaluated at one of the participating centers for being OW or ob, and their initial measurement of liver enzymes were also recorded. The weight status was recorded as body mass index (BMI).…”
Section: Methodsmentioning
confidence: 99%
“…The notion that hepatic inflammation by itself is atherogenic is supported by the observation that CV disease is strongly associated with elevated alanine aminotransferase and γ-glutamyltransferease, which are surrogate markers of liver necroinflammation [9597]. Two large pediatric studies showed an association between elevated serum alanine transaminase levels and the prevalence of the MS and IR as markers of CV risk in obese children aged 3–18 years [98,99]. Longitudinal studies are needed to assess the development of adulthood CV disease in these children with abnormal liver enzymes and other risk factors for atherosclerosis.…”
Section: Nafld and Systemic Inflammationmentioning
confidence: 99%